Labor Relations in Ontario Hospitals : A Question of Survival - Isbester, Fraser; Castle, Sandra (Relations industrielles / Industrial Relations, 1971)
The authors examine the sources of the prevalent unrest among Ontario Hospital employees. As the specific causes of the present situation are outlined separately, their inter-relationships are to be borne in mind.